Letter : Situation in Spain - Stolz, George
011-0044-001 INTERNATIONAL FEDERATION OF TRADE UNIONS St/H TELEGRAMS INTERFED—PARIS TELEPHONE INVALIDES 45-88 9, AVENUE D'ORSAY, PARIS-VIIe EXECUTIVE COMMITTEE : President: W. M Citrine, Great Britain Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia General Secretary : W Schevenels AFFILIATED COUNTRIES ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA Letter sit Espagne No. 347 3rd September 1937, Mr. Walter M. Citrine, St. Andrew's Hall, NORWICH Dear Comrade Citrine, SITUATION IN SPAIN: With reference to your letter of the 13th August, regarding the proposed report on Spain, I would inform you that we asked the Spanish National Trade Union Centre to prepare the documents for this publication, and they agreed to collect material and let us have it. Up till now, we have not received anything of this kind from them, so that, as the necessary material was lacking, it had not been possible to publish anything. Yours sincerely, G.Stolz Assistant Secretary: 292/946/11/44